Analisis Keberlanjutan Peternakan Sapi Perah di Wisata Agro Istana Susu Cibugary di Pondok Ranggon Cipayung Jakarta Timur - Hasdi, A. A.; Fuah, A. M.; Salundik, Salundik (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2015)
Istana Susu Cibugary Agro Tourism is a dairy farm in DKI Jakarta’s dairy site and known well as one of dairy farm development programs.Hence, a study on sustainability level of this dairy farm is required. The first objective of this study was to analyze the index and sustainability status based on five sustainable dimensions. The analysis used Multi Dimensional Scaling (MDS) Method, called RapDairy and the results were stated in the index and sustainability status. The second objective was to analyze the attributes that affect sensitively on index and sustainability status and the effect of error using Laverage and Monte Carlo Analysis. The results of the study revealed that ecological dimension was in the status of less sustainable (46.01%), economical dimension was sufficient sustainable (67.19%), socio culture dimension was sufficient sustainable (60%), dimension of institutional was less sustainable (43.48%) and dimension of technology was less sustainable (46.46%). Out of the 52 attributes analyzed and there were 15 attributes need to be handled immediately as they affect sensitively on the increase of index and sustainability status with a negligible error in the level of 95% confidence limit.